Exploring the Relation Between Metacognition, Gender, and Personality in Colombian University Students - Gutierrez de Blume, Antonio P.; Montoya, Diana (Psykhe, 2023)
In the present study, the relationship between objective and subjective measures of metacognition, personality traits of the Big Five (extraversion, agreeableness, conscientiousness, neuroticism, and openness) and gender were examined. A convenience sample of 352 university students completed the Metacognitive Awareness Inventory, the Adjectives to Evaluate Personality instrument, and completed 3 domain-specific tests (vocabulary, probabilities, paper folding) along with confidence in performance judgments for each item on these tests. Through a combination of descriptive statistics, zero-order bivariate correlations, simultaneous multiple regression, and a multivariate analysis of covariance, findings indicate that objective and subjective measures of metacognition are weakly related and that subjective measures of metacognition were more strongly related to personality traits. Conscientiousness and openness were the only personality traits that positively predicted metacognition. Gender affected both subjective and objective measures of metacognition, even after controlling for university type (private, public) and perceptions of academic performance (high, low) such that males were more accurate and less biased in their monitoring than females only in mathematical reasoning and they reported higher awareness of their knowledge and regulation of cognition than their female counterparts. Findings support the need to better understand how personality traits and gender affect self-regulated learning skills like metacognition to improve educational practices. <!– [if gte mso 9]> <![endif]–><!– [if gte mso 9]> Normal 0 false false false EN-US JA X-NONE <![endif]–><!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–>